2016
DOI: 10.1002/smll.201601669
|View full text |Cite
|
Sign up to set email alerts
|

DNA Nanostructures Carrying Stoichiometrically Definable Antibodies

Abstract: Targeted drug delivery is one of the key challenges in cancer nanomedicine. Stoichiometric and spatial control over the antibodies placement on the nanomedicine vehicle holds a pivotal role to overcome this key challenge. Here, a DNA tetrahedral is designed with available conjugation sites on its vertices, allowing to bind one, two, or three cetuximab antibodies per DNA nanostructure. This stoichiometrically definable cetuximab conjugated DNA nanostructure shows enhanced targeting on the breast cancer cells, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 58 publications
2
87
0
Order By: Relevance
“…Fan's group found that as a multivalent drug carrier, the TDNs remained substantially intact after culturing in live cells for hours . Setyawati and co‐workers confirmed their superior efficacy on delivery anticancer drug . However, challenges remain in the employment of TDNS for cancer diagnostics and therapy, Recently, most reports focused on the transporting routes and the final destinations of TDNs in cells.…”
Section: Introductionmentioning
confidence: 99%
“…Fan's group found that as a multivalent drug carrier, the TDNs remained substantially intact after culturing in live cells for hours . Setyawati and co‐workers confirmed their superior efficacy on delivery anticancer drug . However, challenges remain in the employment of TDNS for cancer diagnostics and therapy, Recently, most reports focused on the transporting routes and the final destinations of TDNs in cells.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 After the core index and the intervention were evaluated, a systematic experimental design was executed to ensure that the data were reliable. The absorbance and fluorescence of CuS@SiO 2 NPs were pretested to eliminate any interference in the CCK-8 tests and flow analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab and other antibodies have previously been investigated for selective delivery of DOX through EGFR‐mediated endocytosis . In a recent example, various numbers of targeting cetuximab antibody units were conjugated to a DNA tetrahedron (up to three cetuximab molecules per DNA nanostructure). After intercalation of DOX in the structure it was applied to different cell types.…”
Section: Methodsmentioning
confidence: 99%